Effectiveness of post particular prolactin administration on follicle development the count in mice (Mouse muscle) female - Merta, I Wayan; Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to test the effectiveness of postpartum prolactin administration on follicle development in the count in mice (Mouse muscle). This type of research is a true experiment using a completely randomized design (RAL). The sample for this study was mice (Mouse muscle) female strain BALB/C, aged ± 4 months with a body weight between 25-30 gr in a healthy condition and not pregnant. The data obtained was analyzed using the One-way analysis of variance (F test) with a significance level of 0.05, followed by the Least Significant Difference test (BNT. The research results show that the sig. (p) = 0.001< α = 0.05, so it can be concluded that postpartum administration of prolactin has a significant effect on follicular development of the count in mice (Mouse muscle).